2004
DOI: 10.1083/jcb.200312031
|View full text |Cite
|
Sign up to set email alerts
|

Apaf-1 and caspase-9 accelerate apoptosis, but do not determine whether factor-deprived or drug-treated cells die

Abstract: Apoptosis after growth factor withdrawal or drug treatment is associated with mitochondrial cytochrome c release and activation of Apaf-1 and caspase-9. To determine whether loss of Apaf-1, caspase-2, and caspase-9 prevented death of factor-starved cells, allowing them to proliferate when growth factor was returned, we generated IL-3–dependent myeloid lines from gene-deleted mice. Long after growth factor removal, cells lacking Apaf-1, caspase-9 or both caspase-9 and caspase-2 appeared healthy, retained intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
126
2

Year Published

2005
2005
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 29 publications
15
126
2
Order By: Relevance
“…20 Cytochrome c release is the result of the activation of the proapoptotic Bcl-2-family members Bax/Bak. Staining for conformationally activated Bax showed that infection with MVA-DE3L led to Bax activation (Figure 2b).…”
Section: Mva-de3l Activates the Mitochondrial Pathway And Utilises Noxamentioning
confidence: 99%
See 1 more Smart Citation
“…20 Cytochrome c release is the result of the activation of the proapoptotic Bcl-2-family members Bax/Bak. Staining for conformationally activated Bax showed that infection with MVA-DE3L led to Bax activation (Figure 2b).…”
Section: Mva-de3l Activates the Mitochondrial Pathway And Utilises Noxamentioning
confidence: 99%
“…20 Briefly, cells were fixed in 2% formaldehyde, washed consecutively in PBS, BPS/BSA 0.5% and PBS/BSA/Saponin 0.5%. Cells were stained with anticytochrome c mAb in PBS/BSA/Saponin, followed by staining with FITC-labelled goat antimouse Ab (Dianova).…”
Section: Microscopy Immunocytochemistry and Flow Cytometrymentioning
confidence: 99%
“…The only apparent reason for cell death in this timescale is the induction of apoptosis as Apaf-1-and caspase-9-deficient cells also maintain their viability following growth factor deprivation over this timescale. 18 Within the first few days of IL-3 deprivation, bax À/À bak À/À cells decreased in size by half and the size continued to decrease steadily until after several weeks the cells began to die. When examining the metabolic profile for these cells, it was found that the glycolytic rate rapidly declined following IL-3 withdrawal.…”
Section: Cell Survival In the Absence Of Bax And Bakmentioning
confidence: 99%
“…However, when long-term survival of these cells is assessed by examining their clonogenic potential, blockade of the apoptotic pathway downstream of cytochrome c release by inhibition of caspases or by deletion of Apaf-1 or caspase-9 was unable to prevent the eventual death of these cells. [22][23][24] These results implicate the release of cytochrome c from the mitochondria as the commitment point for death in mitotic cells.…”
Section: Resultsmentioning
confidence: 73%
“…These results contrast the observations in many mitotic cells, where cells arrested after cytochrome c release by caspase inhibition or deletion of Apaf-1 or caspase-9 fail to recover even when trophic factors are restored. [22][23][24] The recoverability of sympathetic neurons is dependent on the timely restoration of trophic support, as the commitment point for death in sympathetic neurons in which apoptosis is arrested with caspase inhibition does not correspond with cytochrome c release, but rather with the subsequent loss of mitochondrial membrane potential. 25,37 In the prolonged absence of trophic support, however, sympathetic neurons arrested after cytochrome c release eventually undergo nonapoptotic death due to metabolic failure.…”
Section: Discussionmentioning
confidence: 99%